The Relationship Between Knowledge And Adherence To a Hypertension Diet In The Elderly - Juwariah, Titik; yulianto, Yoyok; Priyanto, Agus; Jayadi, Slamet (Health Gate, 2024)
Hypertension or high blood pressure is one of the non-communicable diseases caused by lifestyle. One prevention so that complications do not occur is to change lifestyle, food intake and routine blood pressure control. The purpose of this study was to determine the correlation of level knowledge and elderly hypertension diet adherence in Nganjuk Regency This research design used was correlative with a cross-sectional approach. The population was 28 hypertension elderly people who actively participated in the elderly Posyandu of Cepoko Village the sample all of 28 people as taken by total sampling. The independent variable is the level of knowledge in hypertension, the dependent variable was Elderly Hypertension Diet Adherence. Data collection was carried out using questionnaires. The data was analysed by Spearmen Rank Correlation test with an alpha of 0.05. The results of the study found that 67.86% of respondents including compliant and 32.14% non- adherence, following the hypertension diet and the results of the calculation of SPSS 25 significance value of 0.000, meaning was Ho rejected.  The conclusion of this study was there are The Correlation of Level Knowledge and Elderly Hypertension diet adherence In Nganjuk Regency For this reason, it is hoped that the increasing role of families, cadres and nurses providing health education through interesting information such as using audiovisual such as social media content will be very capable of influencing knowledge that ultimately changes behaviour and compliance with something. Keywordslevel of knowledge, diet adherence, elderly hypertension